2002
DOI: 10.1093/humrep/17.11.2839
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bisphenol A concentrations in human biological fluids reveals significant early prenatal exposure

Abstract: These results suggest accumulation of BPA in early fetuses and significant exposure during the prenatal period, which must be considered in evaluating the potential for human exposure to endocrine-disrupting chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
496
0
8

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 800 publications
(535 citation statements)
references
References 29 publications
21
496
0
8
Order By: Relevance
“…BPA is produced at a value of 1.7 billion kg per annum worldwide and used in the manufacture of several very ordinary products (4). BPA discharged into the environment is expected to break down fairly rapidly in air, whereas it is more persistent in water (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…BPA is produced at a value of 1.7 billion kg per annum worldwide and used in the manufacture of several very ordinary products (4). BPA discharged into the environment is expected to break down fairly rapidly in air, whereas it is more persistent in water (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the levels detected in pregnant women were typically higher than those reported for nonpregnant adults; several studies that used analytical chemistry to assess BPA concentrations measured mean concentrations in the blood or serum from pregnant women at > 4 ng/ mL (Lee et al 2008;Padmanabhan et al 2008;Schönfelder et al 2002). However, only two studies collected samples from pregnant and nonpregnant women and directly compared them using identical methods; one reported slightly lower levels in pregnant women (Ikezuki et al 2002), and the other found no differences in these two populations (Kuroda et al 2003). Thus, this is also an important area for future research.…”
Section: Healthymentioning
confidence: 99%
“…Seventeen studies have measured BPA in blood and serum samples from healthy male and nonpregnant female adults (Dirtu et al 2008;Fung et al 2000;He et al 2009;Hiroi et al 2004;Ikezuki et al 2002;Inoue et al 2000Inoue et al , 2001Kaddar et al 2009;Kuroda et al 2003;Liu et al 2007;Sajiki et al 1999;Sugiura-Ogasawara et al 2005;Takeuchi and Tsutsumi 2002;Takeuchi et al 2004;Volkel et al 2005;Yang M et al 2009;Yoshimura et al 2002) (Table 3). Of these studies, five used ELISA, one used a radioimmunoassay (RIA), and the remainder used analytical chemistry to assess BPA concentrations.…”
Section: Internal Dosage Assessment From Blood Measures Of Bpamentioning
confidence: 99%
See 2 more Smart Citations